Can Biochar Made from Rice Husk Affect Savanna Soils’ pH, Electrical Conductivity, and Soil Respiration? - Ammal Abukari; Prince Cobbinah (Turkish Journal of Agriculture: Food Science and Technology)
Biochar is now gaining awareness as a sustainable tool for soil health improvement, boosting carbon (C) storage and the enhancement of nutrient cycling in agricultural soils. This study assesses the effects of biochar on soil respiration, pH, and electrical conductivity (EC) in savanna soils over a 45-day incubation trail in the laboratory. Four different biochar treatments (0, 2, 4, and 6 t/ha) were used in the study. The treatments were established at 26°C, and after 2, 5, and 10 days, the CO2 levels were recorded. After incubation for 0, 5, 10, and 45 days, the EC and pH were assessed. As the rate of application of biochar increased, the rate of CO2 evolution increased as well. During the first two days of incubation, the CO2 evolution rate rose by a value of 129 at 2 t/ha biochar, 146 at 4 t/ha biochar, and 168 ug CO2/g soil/d at 6 t/ha biochar above the 0 t/ha biochar. Following five days of incubation, the amounts of CO2 evolution that were higher than the control were 99 with 2 t/ha, 116 with 4 t/ha, and 120 ug CO2/g soil/d with 6 t/ha of biochar. The increase in CO2 evolution above the control treatment at 10 days of incubation was 61 with 2 t/ha, 79 with 4 t/ha, and 87 ug CO2/g soil/d with 6 t/ha of biochar. Analogously, rising patterns in CO2 emissions were noted. Throughout the whole incubation period, the biochar treatments' soil EC and pH were greater than those of the control treatment. After applying biochar, there were increases in the evolution of CO2, however after 10 days of incubation, the percentage of C evolved from the addition of biochar decreased as the rates of biochar increased. At two t/ha, four t/ha, and six t/ha, the percentage C developed was 1.74 %, 1.66%, and 0.82% of the applied biochar C, respectively. Although the CO2 evolved ratio to the total amount of biochar C typically reduced with increasing biochar rates, this study shows that the addition of biochar increases soil respiration, EC, and pH.